THE RELATIONSHIP FAMILY SUPPORT AND BLOOD SUGAR LEVELS IN DIABETES MELLITUS SUFFERERS TYPE 2 - Disa Dwi Azahra; Yunisman Roni; Nopriadi (Jurnal SMART Keperawatan, 2025)
Introduction: Type 2 diabetes mellitus (Type 2 DM) is a chronic disease whose prevalence continues to increase globally, including in Indonesia. Diabetes management requires family support which plays an important role in controlling the sufferer's blood sugar levels. Objective: The purpose of this study is to determine how blood sugar levels and family support relate to Type 2 DM patients at the Simpang Tiga Pekanbaru Community Health Center. Methods: This study was conducted at Simpang Tiga Health Center Pekanbaru using cross-sectional method and correlational design. Sampling was done by purposive sampling by selecting 97 people with type 2 diabetes mellitus as samples. Glucometer was used to test blood sugar levels and Hensarling Diabetes Family Support Scale (HDFSS) questionnaire was used to measure family support. Fisher Exact Test statistical technique was used for data analysis. Results: Of 97 respondents, 51 (52.6%) had DM for less than 10 years, and 46 (47.4%) for more than 10 years. Additionally, 53.6% of respondents reported good family support, while 61.9% had uncontrolled blood sugar (>200 mg/dL). Fisher Exact Test showed a significant relationship between family support and blood sugar levels (p=0.037). Conclusion: Blood sugar levels in people with Type 2 DM are significantly correlated with family support. The best possible family support will help control blood sugar levels and avoid problems from diabetes.